Decolonizing the study of English literature in a Muslim-Malaysian context: an argument for a spiritual-based comparative paradigm - Mohd Ramli, Aimillia (Versita, Warsaw, 2013)
The study of English literature was first introduced to the British colonies and protectorates, including Malaysia, in order to consolidate the cultural superiority of the English people amongst the colonized natives. Its continuation in the post-colonial period of the twenty-first century, either as a component of the English language subject at Malaysian secondary schools or as a degree program at Malaysian universities, has mainly been justified by the liberal-humanistic belief that canonical works in English literature display universal values that should be cultivated in the minds of readers regardless of their nationality or religion. In the past few decades, confusion surrounding the exact nature of these values has resulted in the advent of materialistic philosophies of literary theory. In many Muslim countries, such as Ma-laysia, these theories have only served to increase reliance on Eurocentric readings of literature, ignoring resistance coming from Muslim readers who have their own Tawhidic spiritual outlook and values. This paper suggests the use of a paradigm that places a concern for spiritual matters at the core of comparative studies of Eng-lish and Islamic literature, especially at Islamic educational institutions. This can benefit Muslims worldwide in the sense that it will present for them a more com-prehensive role than literature alone can play in contributing to their spiritual devel-opment as well as generating appreciation for the universality of Islamic teachings. Keywords: English literature, comparative, Tawhid, Islam, Malaysia